2010
DOI: 10.1111/j.1740-0929.2009.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fat supplementation during transition period on plasma leptin and non‐esterified fatty acid concentrations in Holstein cows

Abstract: The objective of this experiment was to investigate the effect of fat supplementation during the transition period on pre and postpartum body weight (BW), body condition score (BCS), non-esterified fatty acids (NEFA), glucose and leptin concentrations in Holstein cows. Holstein cows (n = 15) received a low fat diet (LF; 1.61 Mcal net energy for lactation (NEL)/kg of dry matter [DM]), moderate fat diet (MF; 1.68 Mcal NEL/kg DM) or a high fat diet (HF; 1.74 Mcal NEL/kg DM) for 4 weeks prior to calving. All cows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
4
6
0
Order By: Relevance
“…However, prepartum DMI was significantly decreased with CAN and tended to decrease with SUN treatments. These findings are in general agreement with some (Moallem et al, 2007;Duske et al, 2009;Karimian et al, 2015) but not all (Afzalzadeh et al, 2010;Hayirli et al, 2011) reports of reduced DMI with prepartum fat supplementation. The inconsistencies among studies could likely be due to the amount and types of fat sources.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, prepartum DMI was significantly decreased with CAN and tended to decrease with SUN treatments. These findings are in general agreement with some (Moallem et al, 2007;Duske et al, 2009;Karimian et al, 2015) but not all (Afzalzadeh et al, 2010;Hayirli et al, 2011) reports of reduced DMI with prepartum fat supplementation. The inconsistencies among studies could likely be due to the amount and types of fat sources.…”
Section: Discussionsupporting
confidence: 93%
“…Plasma concentrations of cholecystokinin, GLP-1 and glucose dependent insulinotropic peptide were reported to be greater postpartum than prepartum in Holstein cows (Relling and Reynolds, 2007b;Larsen et al, 2010;Hayirli et al, 2011), whereas insulin and leptin concentrations were greater pre-compared with postpartum (Liefers et al, 2003;Kokkonen et al, 2005;Afzalzadeh et al, 2010). However, little is known of the effects of prepartum high fat diets on gut hormone concentrations.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…High and prolonged insulin and Insulin–like growth factor I (IGF‐I) concentrations are critical for follicle and oocyte maturation and quality (Quesnel, Rodriguez‐Martinez, Vallet, & Ziecik, ). However, blood insulin levels can be decreased due to the low total content of carbohydrates in high‐fat diets (Afzalzadeh, Palizdar, Mahmoudzadeh, & Niasari‐Naslaji, ). Dextrose is a readily absorbable carbohydrate that can raise plasma insulin concentration quickly after ingestion (Wientjes et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have reported no effect of soybean oil supplementation on milk protein content (Zheng et al, 2005;Bu et al, 2007). In another study Afzalzadeh et al, (2010) revealed that feeding fat at prepartum period may help animals to use fat sources for energy requirements and consequently other sources of energy such as amino acids (glucogenic precursors) could be used for other functions like protein synthesis and milk production. Likely due to increase milk production, milk protein yield was significantly (P < 0.05) greater by cows fed fat treatments than cows fed CON treatment.…”
Section: Milk Protein Contentmentioning
confidence: 98%